2000
DOI: 10.1177/109980040000200106
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Overload Cardiomyopathy: Evidence for a Free Radical– Mediated Mechanism of Injury and Dysfunction in a Murine Model

Abstract: Iron-overload cardiomyopathy is a restrictive cardiomyopathy that manifests itself as systolic or diastolic dysfunction secondary to increased deposition of iron in the heart and occurs with common genetic disorders such as primary hemochromatosis and beta-thalassemia major. Although the exact mechanism of iron-induced heart failure remains to be elucidated, the toxicity of iron in biological systems is believed to be attributed to its ability to catalyze the generation of oxygen-free radicals. In the current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 43 publications
2
47
0
1
Order By: Relevance
“…This reaction is not only restricted to cell membrane phospholipids, but also to other membrane-bound cellular organelles. By studying iron overload in cultured NRVMs, Link et al (54) demonstrated evidence of lipid peroxidation, reduction in polyunsaturated fatty acids (PUFAs) and increased products from cellular lipid peroxidation, particularly toxic aldehydes (47,53,55,56). The aldehyde products such as malondialdehyde and 4-hydroxynonenal can form a covalent link to proteins (aldehyde-protein adducts), rendering the loss of cellular protein function (57).…”
Section: Evidence Of Iron-mediated Cardiomyocyte Damagementioning
confidence: 99%
“…This reaction is not only restricted to cell membrane phospholipids, but also to other membrane-bound cellular organelles. By studying iron overload in cultured NRVMs, Link et al (54) demonstrated evidence of lipid peroxidation, reduction in polyunsaturated fatty acids (PUFAs) and increased products from cellular lipid peroxidation, particularly toxic aldehydes (47,53,55,56). The aldehyde products such as malondialdehyde and 4-hydroxynonenal can form a covalent link to proteins (aldehyde-protein adducts), rendering the loss of cellular protein function (57).…”
Section: Evidence Of Iron-mediated Cardiomyocyte Damagementioning
confidence: 99%
“…However, excess iron levels can lead to increased reactive oxygen species (ROS) production via the Haber-Weiss and Fenton reactions (Bartfay & Bartfay, 2000;Lekawanvijit & Chattipakorn, 2009). High ROS production can damage cellular lipids, proteins, DNA and mitochondria (Bartfay & Bartfay, 2000;Lekawanvijit & Chattipakorn, 2009). Previous studies suggested that mitochondrial dysfunction could be responsible for cardiac failure resulting from chronic iron overload (Gao et al 2009(Gao et al , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Before DFO After DFO Chronic iron overload produces heart dysfunction in a dose-dependent manner (8), probably resulting from the time lag necessary to deposit iron in tissues. In the heart, iron, initially deposited in the epicardium, has a long term-effect on transmural wall thickness (23,24).…”
Section: Groupmentioning
confidence: 99%
“…Nevertheless, iron overload has undeniably been associated with cardiac and vascular dysfunctions in experimental conditions (5)(6)(7). Experiments conducted ex vivo have shown that iron overload induces a condition of heart failure (8) in Langendorff preparations of isolated hearts. In fact, deposition of iron into the heart is emerging as an important cause of heart failure (6).…”
Section: Introductionmentioning
confidence: 99%